2014
DOI: 10.2147/ijn.s47351
|View full text |Cite
|
Sign up to set email alerts
|

Flower-shaped ZnO nanoparticles synthesized by a novel approach at near-room temperatures with antibacterial and antifungal properties

Abstract: Due to enormous applications of metal oxide nanoparticles in research and health-related applications, metal oxide nanoparticles are increasingly being developed through cheaper and more user-friendly approaches. We have formulated a simple route to synthesize zinc oxide nanoparticles (ZNPs) by a sol–gel method at near-room temperatures 25°C, 35°C, 55°C, and 75°C. The results are analyzed by X-ray diffraction, scanning electron microscopy with energy-dispersive X-ray spectroscopy, and ultraviolet-visible absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 55 publications
(36 reference statements)
2
59
0
1
Order By: Relevance
“…Some nanoparticles as silver induce apoptotic cell death in C. albicans by increasing of hydroxyl radicals [16]. However, shape of nanoparticle can influence its antimicrobial effects [17]. GarciaSaucedo et al investigated the toxicity of SiO 2 nanoparticles on yeast Saccharomyces cerevisiae, and showed that this nanoparticle is low effective or no effective on this yeast [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some nanoparticles as silver induce apoptotic cell death in C. albicans by increasing of hydroxyl radicals [16]. However, shape of nanoparticle can influence its antimicrobial effects [17]. GarciaSaucedo et al investigated the toxicity of SiO 2 nanoparticles on yeast Saccharomyces cerevisiae, and showed that this nanoparticle is low effective or no effective on this yeast [18].…”
Section: Discussionmentioning
confidence: 99%
“…500 rpm, 1000 rpm, 1500 rpm and 2000 rpm) were tested for bactericidal and fungicidal activity by disc-diffusion method25 as well as growth inhibition studies against both Gram-positive ( Bacillus subtilis ) and Gram-negative ( Escherichia coli ) bacteria as well as fungi ( Candida albicans ) as standardized in our lab16. In paper disc diffusion, diluted bacterial culture (0.1 mL) was plated uniformly with the help of a spreader on nutrient agar (NA) plates.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous methods including precipitation technique [9], microwave decomposition [10], hydrothermal process [11], wet chemical method [12] and solgel method [13] have been adopted to produce ZnO nanoparticles (NPs) with different morphologies and characteristics. Studies have reported the production of ZnO-NPs in different forms like flowershaped [14], spherical [15], cubic [16], rice-shaped [10] and nanorods [17]. ZnO-NPs synthesis from diverse resources such as Ziziphus nummularia leaf extract [5], starch [18], gum tragacanth [13], Catharanthus roseus leaf extract [19], honey [7], brown microalga [20] and seaweed [21] have been described previously.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO-NPs synthesis from diverse resources such as Ziziphus nummularia leaf extract [5], starch [18], gum tragacanth [13], Catharanthus roseus leaf extract [19], honey [7], brown microalga [20] and seaweed [21] have been described previously. The properties of ZnO-NPs have been investigated in a wide range of targeted applications including electrical property [22], antibacterial activity [23], antifungal activity [14], catalytic activity [15] and cosmetic industry [21].…”
Section: Introductionmentioning
confidence: 99%